Aloe Vera Extract Is More Effective in Inhibiting the Growth of Enterococcus faecalis Compared to Betel Leaf (Piper betle L.) Extract - Putu Rusmiany; Maya Sari Dewi; Abimanyu Bagas Karo Sebayang (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2026)
Introduction. Oral health is increasingly recognized as critical, as the oral cavity serves as a primary entry point for pathogens, potentially leading to oral diseases and systemic health complications. Materials and Methods. This experimental study employed a post-test only control group design to evaluate the antibacterial efficacy of Piper betle L. (betel leaf) extract compared to Aloe vera extract against Enterococcus faecalis, a key contributor to root canal treatment failure due to its high resistance and persistence in harsh environments. The study aimed to confirm the potential of these extracts as alternatives for managing E. faecalis infections in root canal therapy. Extracts were prepared via maceration using 96% ethanol as solvent, and inhibition zones were measured at 100% concentration against E. faecalis cultured on Mueller-Hinton agar. Results and Discussion. E. faecalis cultures were grown on Mueller-Hinton agar. Both extracts demonstrated inhibitory effects on bacterial growth, with betel leaf extract exhibiting greater efficacy than Aloe vera extract. Conclusion. Betel leaf extract showed superior antibacterial activity against E. faecalis compared to Aloe vera extract, supporting its potential as an adjunct in root canal disinfection. Keywords : root canal irrigation , enterococcus faecalis, betel leaf, aloe vera